Suspect identified: revisiting naming practices in crime coverage - Lillebuen, Steve; Lidberg, Johan; Chubb, Philip (My University, 2016)
This study examines the media's practice of revealing the names of criminal suspects, particularly before charges have been laid. The paper, which uses a content analysis of police stories in two major newspapers in the Australian state of Victoria, shows the practice is commonplace. But as media naming practices extend into online publishing, as observed in this study, unproven police suspicions are given global publicity, causing reputational damage. This paper argues that naming should be considered a significant ethical issue, and one with increasing relevance in the digital age.
Keywords: news media; journalism; naming practices; ethics